Kultum Kamisan as a Strategy to Overcome Limited Allocation of Time for IRE Learning in School - Havida, Nadhiva Iffany; Fahmi, Muhammad; Syaifuddin, Syaifuddin (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2026)
Limited allocation of time for Islamic Religious Education (IRE) or in Indonesia we called Pendidikan Agama Islam (PAI) in public schools is a systemic problem that creates a significant gap between the demands of a comprehensive curriculum and the reality of the available learning time, thus requiring the development of adaptive and innovative strategies to optimize the achievement of learning objectives. This study aims to critically analyze strategies for overcoming the limitations of IRE hours in public schools and to analyze the implementation of the Kultum Kamisan program as a strategy in overcoming the limitations of IRE learning time allocation at SMP Negeri 16 Surabaya. This study has a novelty and uniquely positions of Kultum Kamisan as a program compensation for limited PAI hours, bridging regulatory constraints with comprehensive Islamic education needs.This study uses a qualitative method with a field research approach through participatory observation, in-depth interviews, and documentation, as well as applying the Miles, Huberman, and Saldana triangulation technique to obtain optimal data validity in analyzing solutions to the limitations of IRE learning time allocation at SMP Negeri 16 Surabaya. The results of the study reveal that Kultum Kamisan can be used as an innovative strategy to overcome the limitations of Islamic Religious Education (IRE) learning time allocation. This program not only serves as a supplement to learning time but also as a transformative pedagogical innovation that integrates the strengthening of religious values, character development, and communication skills and self-confidence of students through participatory learning experiences.